STRUCTURAL-—FUNCTIONAL ASPECTS OF THE PINEAL, PITUITARY, OVARY AND UTERUS OF ‎TRYPANOSOMA EVANSI INOCULATED RABBIT - Alnoor , S .; Al-Jibbori ‎, N.; W.R. Mehdi ‎, A. (The Iraqi Journal of Veterinary Medicine, 2024)
This experiment aimed to investigate changes, in the structural-functional aspects of the pineal and pituitary glands as well as the ovary and uterus, that might associate with trypanosomiasis induced by T. evansi in female rabbit. The ovarian and uterine response to the luteinizing hormone-like activity (Human Chorionic Gonadotropin, HCG) was also tested. Trypanosomiasis did not cause significant changes in body, ovarian and uterine weights. There were degenerative changes in the structural-functional picture of the studied organs. T. evansi resulted in decreased response of the ovaries and uteri to HCG. The direct and indirect effects, including somatic and autoantibodies production, of this species of trypanosomes might be responsible for the reported findings.